Assessment of anxiety/depression among cancer patients before and during the COVID‐19 pandemic. Issue 10 (14th September 2022) - Adzrago, David; Sulley, Saanie; Tagoe, Ishmael; Ormiston, Cameron K.; Odame, Emmanuel A.; Mamudu, Lohuwa; Williams, Faustine
Abstract: Objective: To assess differences in the prevalence of anxiety/depression symptoms among cancer patients before (2019) and during the COVID‐19 pandemic (2020); and the associations between anxiety/depression and sociodemographic and health behavior factors among cancer patients before and during the pandemic. Methods: We analyzed data from the 2019 ( n  = 856) and 2020 ( n  = 626) Health Information National Trends Survey, a nationally representative survey of United States adults aged ≥18 years. Only adults with a cancer diagnosis were used in the analyses. Anxiety/depression was assessed using the Patient Health Questionnaire‐4 (low/none [0–2], mild [3–5], moderate [6–8], and severe [9–12]) and dichotomized as low/none and current anxiety/depression (mild/moderate/severe). Multivariate analysis was performed. Results: The prevalence of anxiety/depression symptoms among cancer patients was 32.7% before the COVID‐19 pandemic and 31.1% during the pandemic. The odds of anxiety/depression among patients with fair/poor health status was higher during the pandemic relative to before (before: odds ratio [OR] = 1.85 vs. during: OR = 3.89). Participants aged 50–64 years (before: OR = 0.29, 95% confidence interval [95% CI] = 0.11–0.76; during: OR = 0.33, 95% CI = 0.11–0.97) and ≥65 years (before: OR = 0.13, 95% CI = 0.05–0.34; during: OR = 0.18, 95% CI = 0.07–0.47) had lower odds of anxiety/depression before and during the pandemic compared to those aged 35–49 years. Hispanics/Latinos had higher odds of anxiety/depression (OR = 2.70, 95% CI = 1.11–6.57) before the pandemic and lower odds of anxiety/depression during the pandemic (OR = 0.2, 95% CI = 0.05–1.01) compared to non‐Hispanic Whites. Those who completed high school (before: OR = 0.08, 95% CI = 0.01–0.42), some college (before: OR = 0.10, 95% CI = 0.02–0.42), ≥college degree had lower odds of anxiety/depression symptoms (before: OR = 0.05, 95% CI = 0.01–0.26; during: OR = 0.06, 95% CI = 0.01–0.61) compared to those with less than a high school education. Conclusion: Our results suggest the need to increase the provision of mental health services to cancer patients at high risk of developing anxiety/depression symptoms, particularly during public health emergencies, to alleviate further health burdens.